Pengembangan Buku Cerita Matematis Berbasis Augmented Reality untuk Kemampuan Bernalar Kritis Siswa SD - Ermawati, Diana; Riswari, Lovika Ardana; Hilyana, F Shoufika; Wijayanti, Esti (Jurnal Pendidikan Matematika : Judika Education, 2024)
The purpose of this study was to test the feasibility and effectiveness of media in developing mathematical story books based on augmented reality on the critical reasoning abilities of elementary school students. The research method used is Research and Development (RnD) with the ADDIE development model. The results of the study showed that the validation of the MABARUNG media stated that the media could be used in the learning process as evidenced by the validation results by validator 1 of 94%, and validator 2 of 85%, and the mathematical story book media based on augmented reality was effective for use in mathematics subjects with the material of spatial characteristics. This is evidenced by the results of the N-gain test which obtained a value of 0.79 with a "high" category. In conclusion, the mathematical story book media based on augmented reality can improve the critical reasoning abilities of elementary school students. Keyword: Augmented Reality, Critical Reasoning, Mathematical Storybook